Elucidation of synbiotic diet comprising of Lactobacillus plantarum L20 and Sargassum polycystum on gastrointestinal microbiota, tissue structures and AHPND associated dysbiosis susceptibility in black tiger shrimp (Penaeus monodon) - Chin, Yong Kit; Sayuti, Mohamad Azzam; Mohamad, Aslah; Haryani, Wan Omar Haifa; Ahmad, Mohd Ihsanuddin; Nazarudin, Muhammad Farhan; Mohd Ali, Nur Shidaa; Md Yasin, Ida Muryany; Abd Karim, Murni Marlina; Annas, Salleh; Norhariani, Mohd Nor; Amal, Mohammad Noor Azmai; et al. (Elsevier B.V., 2025)
This study investigates the effect of a synbiotic combination comprising of Lactobacillus plantarum L20 and Sargassum polycystum on gastrointestinal microbiota, tissue structures and AHPND infection in black tiger shrimp, P. monodon. The shrimp were randomly distributed into synbiotic (feed that was incorporated with 108 CFU/g of L. plantarum L20 and 2% S. polycystum) and control group (feed that was incorporated with PBS). After 35 days of feeding trial, all groups were subjected to an AHPND-causing V. parahaemolyticus S2–4 immersion challenge at 6 × 105 CFU/mL. The shrimp gastrointestinal tract from both groups were collected from the feeding trial and challenge test and subjected to high throughput 16S rRNA amplicon sequencing and histopathological analysis. Following 35th day of feeding trial, there were growth enhancement in shrimp, but no significant differences (p > 0.05) in alpha and beta diversities in gastrointestinal microbiota for both groups. However, synbiotic group exhibited a differential abundance of beneficial bacteria, including Lactobacillaceae and Lactiplantibacillus, which were not observed in the control group. Following 60 h post-challenge, there was improvement in shrimp survival in synbiotic group, with slightly significant differences (p < 0.05) were observed in alpha diversity and but no significant differences (p > 0.05) were observed in beta diversity. Synbiotic group demonstrated negative correlation between the gastrointestinal microbiota with Vibrionaceae, enriched potential metabolic pathway of energy generation and microbiota proliferation, and protected gastrointestinal tract structure during the study. The findings suggest that synbiotic diet comprising of L. plantarum L20 and S. polycystum improve growth performance, disease resistance and gastrointestinal structure protection through enhancement of few beneficial bacteria group abundance, despite insignificantly changes of gastrointestinal microbiota with control diet in the shrimp.